Optimizing Warehouse Layout Using Shared Storage at PT BJIC - Hadi, Vidiantoro Putra; Fitriani, Katlea; Irawan, Yeremias Budi (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2026)
This research aims to analyze and provide solutions for PT Best Jeans Indo Citranusa (PT BJIC), which faces Inefficiencies in raw material placement and movement flow due to limited space and suboptimal layouts. Using the shared storage method, the study determines warehouse layout designs, distances, and movement times to propose better alternatives and improve material handling efficiency. The proposed layout was simulated using ProModel to evaluate its effectiveness. The simulation results reveal significant improvements compared to the current layout. The proposed design reduces the movement distance by 57.58 meters, equivalent to a percentage difference of -23.98%. Additionally, the simulation demonstrates a total time reduction of 206.17 minutes, or -55.17%, in transfer flow duration. These findings highlight the potential for substantial efficiency gains in both distance and time. By addressing layout constraints and optimizing the flow of raw materials, this research provides a practical solution for improving warehouse operations. The proposed layout demonstrates high efficiency and offers a significant improvement compared to the existing design, making it a suitable alternative for PT BJIC to overcome its current challenges.